The Dynamics of Earth’s Cusp in Response to the Interplanetary Shock - Jie Ren; Qiugang Zong; Suiyan Fu; Huigen Yang; Zejun Hu; Xiaoxin Zhang; Xuzhi Zhou; Chao Yue; Lynn Kistler; Patrick Daly; Elena Kronberg; Robert Rankin (Universe, 2023)
The Earth’s magnetospheric cusp, a region with an off-equatorial magnetic field minimum, is an important place which directly transports plasma and energy from the solar wind into the magnetosphere and ionosphere. Its magnetic topology and charged particles therein are known to respond to the solar wind and the interplanetary magnetic field. However, its dynamics in response to the interplanetary (IP) shock are still unknown, due to lack of direct spacecraft observations. This study first reports the observations of the cusp’s motion under the drive of an IP shock and both strong electric fields and outflowing energetic ions in the moving cusp. After an IP shock arrival on 7 September 2017, triple cusps were observed by Cluster C4 when it was crossing the high-altitude northern polar region to the sub-solar magnetosphere. The multiple cusps had a one-to-one correspondence with the dayside magnetosphere compression and relaxation detected by THEMIS E, indicating that one cusp moved back and forth three times due to the IP shock’s impact. In the moving cusp, there were strong impulsive electric fields with a peak of up to ∼40 mV/m and an ionospheric source population of upward propagating ions (O<semantics>+</semantics>, He<semantics>+</semantics> and H<semantics>+</semantics>) with energies extending to MeV. However, the outflowing ions outside the cusp had energies of no more than 1 keV. An enhancement of energetic O<semantics>+</semantics> appeared inside the cusp with the flux ratio of O<semantics>+</semantics>/H<semantics>+</semantics> increasing from 10 keV to ∼ MeV, which implies the efficient acceleration of O<semantics>+</semantics>. These observations are shown to be consistent with the prompt acceleration by the impulsive electric fields, which is mass-dependent. This finding suggests a new acceleration mechanism for cusp energetic ions, especially for O<semantics>+</semantics>.